Measuring employment and job quality in agrifood systems: A comprehensive approach - Corong, Erwin; Gautam, Madhur; Martin, Will; Vos, Rob (International Food Policy Research Institute, 2024)
As the agricultural transformation associated with economic development proceeds, the economic fulcrum of the agrifood system moves from on-farm, or primary, production activities to activities that are increasingly non-farm sector based, such as agro-processing, food services, wholesale and retail trade, etc. Therefore, the traditional measures of farm employment and value-addition (or GDP) come to represent a smaller and smaller share of the total contribution of the agrifood system. Better quantification is important not only to appreciate the transformation within the agrifood system with economic development, but also to inform better policies and strategies to create more and better-quality jobs and accelerate structural transformation in developing economies. There are two broad approaches to measuring the size of the agrifood sector—tracking activity in agrifood sectors; and exploiting the full structure of the economy to assess the direct and indirect employment required to meet final demand for agrifood products. Both approaches are used in an analysis based on the global GTAP database and their results compared. The findings suggest that the final demand approach provides a more comprehensive assessment of the economic activities needed to meet final demand, with agrifood sector accounting for a much larger share of GDP, and the broader agrifood sector generating more and better-quality skilled jobs for both male and female workers. Another key aspect of the relationship is the resources needed to produce non-food products such as biofuels, clothing and leather products that rely on agricultural inputs. Including the resources needed to produce non-food agrifood outputs substantially increases the importance of the agrifood sector in overall activity and employment.